The grooved lip effect on reciprocating hydraulic rod seal performances in transient condition: elastohydrodynamic lubrication - Bahi, Youssef; Gadari, Mhammed El; Rahmoune, Miloud (Zielona Góra: Uniwersytet Zielonogórski)
It is commonly known that the sealing performance of dynamic seals is significantly influenced by the surface finish. To reduce friction effect and leakage ratio, new generations of grooved lip or shaft have emerged, but only two computational models were performed up to now with a textured elastomeric lip: spiral groove in the axial direction or micro-cavities according to the circumferential direction.
Keywords: hydraulic rod seal; surface-textured; roughness; friction forces; leakage